Addressing health equity for breastfeeding women: primaquine for Plasmodium vivax radical cure - Nada Abla; Anne Claire Marrast; Elodie Jambert; Naomi Richardson; Stephan Duparc; Lisa Almond; Karen Rowland Yeo; Xian Pan; Joel Tarning; Ping Zhao; Janice Culpepper; Catriona Waitt; et al. (Malaria Journal, 2024)
Abstract Plasmodium vivax malaria remains a global health challenge, with approximately 6.9 million estimated cases in 2022. The parasite has a dormant liver stage, the hypnozoite, which reactivates to cause repeated relapses over weeks, months, or years. These relapses erode patient health, contribute to the burden of malaria, and promote transmission. Radical cure to prevent relapses requires administration of an 8-aminoquinoline, either primaquine or tafenoquine. However, malaria treatment guidelines updated by the World Health Organization (WHO) in October 2023 restrict primaquine use for women breastfeeding children < 6 months of age, or women breastfeeding older children if their child is G6PD deficient or if the child’s G6PD status is unknown. Primaquine restrictions assume that 8-aminoquinoline exposures in breast milk would be sufficient to cause haemolysis in the nursing infant should they be G6PD deficient. WHO recommendations for tafenoquine are awaited. Notably, the WHO recommends that infants are breastfed for the first 2 years of life, and exclusively until 6 months old. Repeated pregnancies, followed by extended breastfeeding leaves women in P. vivax endemic regions potentially vulnerable to relapses for many years. This puts women’s health at risk, increases the malaria burden, and perpetuates transmission, hindering malaria control and elimination. The benefits of lifting restrictions on primaquine administration to breastfeeding women are significant, avoiding the adverse consequences of repeated episodes of acute malaria, such as severe anaemia. Recent data challenge the restriction of primaquine in breastfeeding women. Clinical pharmacokinetic data in breastfeeding infants ≥ 28 days old show that the exposure to primaquine is very low and less than 1% of the maternal exposure, indicating negligible risk to infants, irrespective of their G6PD status. Physiologically-based pharmacokinetic modelling complements the clinical data, predicting minimal primaquine exposure to infants and neonates ...